Biogeochemical Response of Apalachicola Bay and the Shelf Waters to Hurricane Michael Using Ocean Color Semi-Analytic/Inversion and Hydrodynamic Models - D’Sa, Eurico J.; Joshi, Ishan D.; Liu, Bingqing; Ko, Dong S.; Osburn, Christopher L.; Bianchi, Thomas S. (Frontiers in Marine Science, 2019)
Hurricanes are increasingly being recognized as important episodic drivers in ocean biogeochemical cycling; however, spatiotemporal response of their impacts on coastal and estuarine ecosystems are limited. Hurricane Michael, which made landfall just west of Apalachicola Bay (ApB) on October 10, 2018 as a Category 5 hurricane with sustained winds of 250 km h-1, caused widespread damage to the northwest Florida coast, and adverse effects on oyster reefs and water quality in ApB due to winds and coastal flooding associated with a strong storm surge. The impact of wind forcing and retreating storm surges on coastal and shelf biogeochemical properties remains however, largely unknown. In this study, we use a combination of pre-hurricane field observations, ocean-color satellite imagery and the outputs (salinity, currents, sea surface height and temperature) of a nested high-resolution 3-dimensional hydrodynamic model (NCOM) to examine the biogeochemical response of ApB and the surrounding shelf waters to Hurricane Michael. MODIS-derived optical proxies (e.g., absorption of colored dissolved organic matter or CDOM and particle backscattering coefficients) of dissolved and particulate organic carbon (DOC and POC) were derived for a series of clear-sky imagery (prior to and following the hurricane) using a combination of estuarine-tuned semi-analytic and empirical algorithms. Following the hurricane, spatiotemporal distribution of both DOC and POC in ApB and the nearshore coastal waters showed a strong response to storm surge, increasing river discharge, currents, and wind field. Average flux estimates of organic carbon exported from ApB between October 5-21, 2018 to the coastal ocean were much greater for DOC (0.86106 kg C d-1) than POC (0.21106 kg C d-1) and increased with increasing river discharge and the wind field. A bio-optical inversion algorithm applied to Sentinel-3A OLCI imagery of 13 October, 2018 immediately following the hurricane’s passage, showed a strong, week-long biological response with spatially distinct phytoplankton blooms of Karenia brevis and Emiliania Huxleyi, as detected by satellite imagery of pigments, an approach that could revolutionize our understanding of environmental impacts on phytoplankton. This study revealed spatiotemporal changes in estuarine and coastal ocean biogeochemistry reflective of a systematic regional ecosystem response to Hurricane Michael.